The effect of lexical triggers on Spanish-English code-switched judgment tasks - Koronkiewicz, Bryan; Delgado, Rodrigo (Frontiers in Psychology, 2024)
It has been argued that certain words can "trigger" intrasentential code-switching (de Bot et al., 2009). While some researchers suggest that cognates establish triggering at the lexical level (Broersma, 2009;Broersma & de Bot, 2006;Broersma et al., 2009;de Bot et al., 2009), others have argued that words that lack direct translations are "more natural to switch" (González-Vilbazo et al., 2013, p. 8). Yet to be tested experimentally is to what extent different types of lexical items influence the acceptability of mixed utterances. The current study investigates this methodological consideration for code-switching research by having early US Spanish-English bilinguals (i.e., heritage speakers of Spanish) complete an acceptability judgment task with a 7-point Likert scale, directly comparing cognates (e.g., sopa 'soup') and culturally specific items (e.g., pozole 'traditional Mexican soup') in otherwise identical grammatical switched sentences (N = 24). The results showed that there was no significant effect of condition (p = .623), suggesting that cognates and languagespecific items are equally acceptable in code-switched sentences. Indeed, all conditions were rated on average above 6. These findings show that, in this context, judgment tasks are not affected differently by these types of lexical items.